AN APPLICATION OF OPTIMIZATION IN DISTANCE AND TIME TRAVEL OF SOLID WASTE COLLECTION IN TANGERANG MUNICIPALITY - Radhitya Martha Eka Dewi; Yori Herwangi (Built Environment Studies, 2023)
Solid waste management has become a major challenge due to strong urban population growth in many developing countries. As one of Indonesia's highest-density population cities, Tangerang City faces the disorganization of the solid waste management system handled by the government. This study aims to create an alternative solid waste disposal transportation by modelling the route and the number of trips. The initial step in reducing the unnecessary distance is redesigning the landfill area's vehicle pool. The vehicles should start and end the activity at the landfill. The calculation of OD pair distance uses Google API in the specific departure time by inputting coordinate data such as longitude and latitude. The application simultaneously applied the documentation of distance and time to 338 waste collection points. The data result is compiled in the distance matrix to find the closest destination between the collection point. The combination of collection points must meet the capacity requirement. Lastly, the new vehicle task is taken from the optimized routes. Compared to the current system, the new collection plan can achieve a reduction of 8% in the distance driven and 4% in the collection time. The development model is beneficial in shortening the distance driven and the travel time.